Answer:I think that it would be either b or c
Step-by-step explanation:
(-1,9) because Y is always the second number and -3*-1=3 so 9=3+6 basically :)
Answer:
(2x + y)(2x - y)
Step-by-step explanation:
1. Simplify the square 4x²:
(2x)² - y²
2. Apple the difference of two squares formula <em>x² - y² = (x + y)(x - y)</em>:
(2x + y)(2x - y)
hope this helps!
<h3>
Answer: Choice D</h3>
Domain = [-3, infinity)
==================================================
Work Shown:
In step 2, we replaced every x with g(x)
In step 3, we plugged in g(x) = sqrt(x+3)
The domain of g(x) is [-3, infinity), so this is the domain of as well since the composite function depends entirely on g(x). Put another way: the input of f(x) depends on the output of g(x), so that's why the domains match up.
Answer:
Choices C and D
Step-by-step explanation: